The p.Gly130Val mutation in the GJB2 gene: A familiar case of autosomal dominant non-syndromic hearing loss. (December 2019) - Bussini, Adelaide; Righi, Rossana; Pessina, Chiara; Genoni, Angelo; Cristofari, Eliana; Meli, Annalisa; Granata, Paola; Meroni, Emanuela; Broccolo, Francesco; Casalone, Rosario
Abstract: Several forms of sensorineural hearing loss (SNHL) have been imputated to connexins mutations and prevalently to connexin 26 (Cx26), codified by the GJB2 gene (gap junction protein, beta 2). Here, we report the first familiar case (heterozygous p. G130V mutation) of non-syndromic (without any dermatological manifestation) dominant profound SNHL. Proband was a 6-years-old male with post-lingual bilateral profound SNHL, clinically identified at the age of 3 with diagnosis of severe SNHL. We confirm that the p. G130V variant of the GJB2 gene is causative of autosomal dominant form of SNHL, although it is not always associated with the presence of skin diseases.